Two new species of the ‘Big Yellows’ (Diptera: Sarcophagidae: Sarcophaga) - Geisler, Lucas; Pape, Thomas (Zootaxa, 2023)
The informal name ‘Big Yellows’ is proposed for a possibly non-monophyletic assemblage of large-bodied, yellow-coloured species of flesh flies found in the Melanesian archipelagoes of Bismarck, Solomon and Vanuatu. The group comprises several species of Sarcophaga Meigen subgenus Sarcorohdendorfia Baranov plus the only species of Sarcophaga subgenus Chrysosarcophaga Townsend. Two new species are described from Melanesia: Sarcophaga (Sarcorohdendorfia) confusio sp. nov. (Bismarck Archipelago: New Britain, Yalom) and S. (S.) narabondxii sp. nov. (Solomon Islands: Nggele Islands). A key to the species of this group is provided, and their distribution is summarised. The subgenus Sarcorohdendorfia is diagnosed, and the presence of a single row of downward-facing setae along the ventral margin of the mesopleural anatergite is suggested as an important diagnostic feature. Sarcorohdendorfia Baranov, 1938 is proposed as a senior synonym of Omarisca Kurahashi, Tan & Leh, 2021, syn. nov., and Chrysosarcophaga whitneyi Curran, 1936 is proposed as a senior synonym of Sarcorohdendorfia imitatrix Baranov, 1938, syn. nov. Sarcophaga aureolata Pape & Kurahashi, 2000, S. pattoni Senior-White, 1924 and S. saprianovae Pape & Bänziger, 2000 are transferred from the subgenus Lioproctia Enderlein, 1928 to the subgenus Sarcorohdendorfia Baranov, 1938.